PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI DAN KEAHLIAN PEMAKAI TERHADAP KUALITAS INFORMASI AKUNTANSI (STUDI EMPIRIS PADA PEMERINTAH KABUPATEN MINAHASA SELATAN) - Jansen, Cornelia Ferny; Morasa, Jenny; Wangkar, Anneke (Universitas Sam Ratulangi, 2018)
Information is the result of data processing that gives meaning and benefit. Thus, information systems have an important role in relation to the quality of accounting information. The growing information system used then the resulting information will be better and will provide various facilities on the activities of government agencies in order to improve the quality of accounting information. This study aims to determine how the influence of the use of information technology and user expertise on the quality of accounting information. The sample in this research consist of 30 SKPD in South Minahasa Regency. Data analysis technique used is multiple linear regression analysis. The results showed that the use of information technology has a significant positive effect on the quality of accounting information as well as the expertise of users who have a significant positive effect on the quality of accounting information.Keywords : Information, Information Technology, User Expertise, Quality Accounting Information